Staphylococcus aureus, including Community-Acquired Methicillin-resistant S. aureus, in a Level III NICU: 2001 to 2008 - Rana, Divya; Abughali, Nazha; Kumar, Deepak; Super, Dennis M.; Jacobs, Michael R.; Kumar, Mary L. (American Journal of Perinatology, 2012)
Objective To determine epidemiology and clinical characteristics of infants with methicillin-susceptible (MSSA) and -resistant Staphylococcus aureus (MRSA) in a level III neonatal intensive care unit (NICU).Study Design All NICU admissions (2001 to 2008) with any positive S. aureus culture were included as cases. Cases were further characterized as either colonized or infected with invasive disease.Results Four thousand three hundred four infants were admitted; 273 (6.3%) had at least one culture positive for S. aureus, including 198 with MSSA and 75 with MRSA. Invasive disease occurred in 23.2% of MSSA cases versus 29.3% MRSA (p = 0.298). Between the study periods 2001 to 2005 versus 2006 to 2008, the incidence of all MSSA cultures (colonization and invasive disease) decreased from 53.6 to 38.9/1000 admissions (p = 0.044), and that of MRSA increased from 13.7 to 24.77/1000 admissions (p = 0.010). The incidence of invasive MSSA (p = 0.49) and MRSA (p = 0.38) disease between the two periods remained similar. Infants with invasive MRSA versus MSSA had a longer duration of positive cultures (55 versus 19 days, p = 0.009). None of five available isolates collected prior to 2006 was characterized as USA300, but 11/21 isolates collected subsequently were USA300 (p = 0.053).Conclusion The incidence of MRSA (colonization and infection) nearly doubled during the study period coinciding with emergence of community-acquired MRSA USA300.
Keywords: Staphylococcus aureus; MRSA; preterm; NICU